Penerapan Model Example Non Example untuk Meningkatkan Hasil Belajar Kelas V SDN 57 Kaca - Ritha Tuken; Shasliani Shasliani; Jurana Jurana (STKIP Andi Matappa Pangkep, 2023)
The problem in this research is the low learning outcomes in class V students of UPTD SPF Negeri 57 Kaca Soppeng district. The purpose of this study was to determine the process of applying the example non example cooperative learning model and to find out the application of the non example type example cooperative learning model to improve student learning outcomes about unity and integrity. The approach used is a qualitative approach. Data collection techniques used are observation, tests, and documentation. The research subjects were classroom teachers and students who collected 24 students consisting of 18 male and 6 female students. In the first cycles, the results of the research on the learning process were sufficient qualification (C) and the learning test results were in sufficient qualification (C). II the results of research on the learning process are in good qualification (B) and learning test results are in good qualification (B). The conclusion in this study is that the application of the example non example cooperative learning model can improve the process and students' learning outcomes about unity and integrity in class V UPTD SPF Negeri 57 Kaca, Soppeng district.